Mérito, estabilidade e desempenho - influência no comportamento do servidor público - Souza, Teresa Cristina Padilha de (2002)
This essay has the purpose of identifying the influence of merit, tenure rights and perfonnance on the behavior of the Brazilian civil servant. The lack of an efficient merit-based system, the handicaps in the application and the adequacy of perfonnanceevaluation mechanisms, the concession of tenure rights, as well as distortions of bureaucracy, area pointed out as the most relevant elements responsible for the loss of stimuli for the civil servant, the decrease on perfonnance leveIs in the public sector, and the consequent loss of credibility from the Brazilian people, users of public services. The theoretical fundamentaIs are based on Theory of Administration, Theory of Motivation, Theory of Bureaucracy and Organizational Culture, since they are closely related to the subject in study. In order to have a better understanding about social and cultural origins of the problem, a historic retrospect is presented, relating to public employment in our country, starting from the colonization period, up to today, focusing on merit, perfonnance and tenure rights, as precepts of the Brazilian Constitutions, and their effects upon the actual legal regime regarding human resources of the public service. The real concepts, meanings and purposes of these precepts are brought up, enforcing the need for their existence, while focusing on their distortions, mainly conceming tenure rights and public bureaucracy. The main proposals on administrative refonns are also shown, with emphasis on a possible flexibility conceming tenure rights. After presenting some suggestions and proposals towards solutions for some of the problems brought up, the study concludes that is indispensable for the public administration to have merit as the basis for ingress and evolution in the careers of the public sector, in addition to searching for the constant improvement of legitimized perfonnance-evaluation mechanisms, in order to encourage and stimulate high leveIs of perfonnance and creativity. In the same way, it emphasizes the role of tenure rights in the protection of the public sector against nepotism and political preferences, and depicts the relevance of some aspects of public bureaucracy, as key-elements of a good merit-based system.